Circulating biomarkers of CNS tumors: an update. (April 2013) - Ilhan-Mutlu, Aysegül; Wagner, Ludwig; Preusser, Matthias
CNS tumors comprise approximately 120 histological subtypes. Advances of surgical resection, radiation and systemic therapy have increased the survival rates of distinct types of CNS tumor patients. There is growing interest in identification of diagnostic, prognostic or predictive blood biomarkers in CNS tumor patients, and emerging studies indicate that certain brain tumors are indeed associated with distinct profiles of circulating factors such as proteins (e.g., glial fibrillary acidic protein), DNA fragments (e.g., containing mutated IDH ) or miRNAs (e.g., miRNA-21). However, blood biomarker research in neurooncology is, for the most part, at an exploratory level, and adequately powered and well-designed studies are needed to translate the available interesting but preliminary findings into actual clinical use. In this review, the current knowledge on circulating biomarkers of CNS tumors is briefly summarized.